Mucinous adenocarcinoma and non-mucinous adenocarcinoma: differing clinicopathological characteristics and computed tomography features in gastric cancer - Zhao, Jianxi (Oncotarget, 2017)
Mucinous gastric carcinoma (MGC) is a rare histological subtype of gastric cancer. The clinicopathological characteristics and CT features of MGC remain controversial. This study aimed to determine the clinicopathological characteristics and CT features of MGC. We reviewed 62 patients with MGC and 104 patients with non-mucinous gastric carcinoma (NMGC), pathologically confirmed between 2003 and 2015. There are significant differences in some clinicopathological characteristics and CT features between MGC and NMGC. NMGC occurs preferentially in males and more frequently in the lower third of the stomach. Patients with MGC were characterized by larger tumor size, more advanced tumor stages (II and III) and fewer lymphatic invasions. Layered enhancement (83.3%) was the main pattern of MGC, while the most common pattern in NMGC was homogeneous enhancement (52.6%), followed by heterogonous enhancement (34.6%). The degree of enhancement of the inner layer in MGC was significantly higher than in NMGC (ΔCT of portal venous phase: 54.57 Hu vs. 47.19 Hu, P = 0.034), while the middle or outer layer in MGC was significantly less enhanced (ΔCT of portal venous phase: 19.07 Hu vs. 33.09 Hu, P <0.001). Calcifications were more common in MGC (P <0.001). ROC curves revealed that the most effective variables in distinguishing MGC and NMGC were ΔCT of the middle or outer layer in the arterial phase (AUC=0.774) and portal venous phase (AUC=0.774), followed by the attenuation value of the middle or outer layer in the unenhanced phase (AUC=0.763). Calcifications had a high specificity (98.7%) in the diagnosis of MGC. The accuracy (86.1%), sensitivity (83.3%) and specificity (87.2%) of layered enhancement in diagnosing MGC were all high. Therefore, MGC was more likely to have larger tumor size and more advanced tumor stage (II and III) than NMGC. The thicker gastric wall, layered enhancement pattern and calcification were highly suggestive CT features for differentiating MGC from NMGC.